2015
DOI: 10.1016/j.addbeh.2014.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Normative perceptions of non-medical stimulant use: Associations with actual use and hazardous drinking

Abstract: Approximately 10% of US college students are engaged in non-medical use of prescription stimulants (NMUPS) and that use is linked to concerning health, educational, and societal consequences. Few studies have assessed normative perceptions surrounding NMUPS. Accordingly, we examined self-reported use and normative perceptions for NMUPS and demographic factors that may be associated with them. We also investigated whether higher normative perceptions for NMUPS were related to the most commonly used and abused s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 38 publications
(48 reference statements)
3
15
0
3
Order By: Relevance
“…In our study, an association between perceived injunctive norms of peers and students' personal approval of using NPPSSP was found for all countries participating in the SNIPE project, except for the UK, with its comparatively small sample size. The findings of this study align with previous observations that university students' exaggerated perceptions of peer norms also exist for prescription substances which are less commonly used and socially accepted than, for example alcohol, tobacco, or cannabis (Helmer, et al, 2016;Kilmer, et al, 2015;McCabe, 2008;Perkins, et al, 1999;Sanders, et al, 2014;Silvestri & Correia, 2016).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, an association between perceived injunctive norms of peers and students' personal approval of using NPPSSP was found for all countries participating in the SNIPE project, except for the UK, with its comparatively small sample size. The findings of this study align with previous observations that university students' exaggerated perceptions of peer norms also exist for prescription substances which are less commonly used and socially accepted than, for example alcohol, tobacco, or cannabis (Helmer, et al, 2016;Kilmer, et al, 2015;McCabe, 2008;Perkins, et al, 1999;Sanders, et al, 2014;Silvestri & Correia, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have examined misperceptions or self-other discrepancies about the non-medical use of prescription drugs, as well as associations between descriptive norms and personal use, particularly regarding prescription stimulants (Helmer, et al, 2016;Kilmer, Geisner, Gasser, & Lindgren, 2015;McCabe, 2008;Sanders, Stogner, Seibert, & Miller, 2014;Silvestri & Correia, 2016), with only one study, to date, investigating prescription sedative use (Sanders, et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This use has expanded the social network of young adults, and online platforms may have more influence on their substance use than actual in-person interactions [ 5 , 6 ]. Historically, college students have perceived that their peers used substances more than they actually do [ 7 - 9 ]. As such, exposure to substance use via social media may normalize the use for some young adults by presenting it in a positive light, potentially providing a skewed perspective compared to the actual behavior of most college-aged persons.…”
Section: Introductionmentioning
confidence: 99%
“…Parental substance use, childhood perceptions of parental norms, and individual and friends’ norms all contribute to an increased likelihood of marijuana and alcohol use [24]. Research on prescription drug norms has found individuals to overestimate peers’ misuse [33]. …”
Section: 0 Introductionmentioning
confidence: 99%